Advanced Fault Ride Through Operation of Grid-Forming Voltage Source Converters Using a Model Predictive Controller - Mahr, Florian; Jäger, Johann (Energy Conversion Congress & Exposition - Asia (ECCE-Asia), 2021)
An advanced fault ride through (FRT) operation mode of grid forming voltage source converters (VSC) using a finite control set model predictive control (FCS-MPC) algorithm is presented. Grid-forming VSCs are essential for weak distribution grids and islanded microgrids. The FRT operation of VSCs is requisite to avoid damages and to guarantee a resilient grid operation during balanced and unbalanced grid faults. FRT operation based on conventional cascaded control loops shows problems concering stability and the practical application. In this paper, a new definition of the FCS-MPC cost function allows to manage both current limiting and grid support. Beyond that, the fault is detected locally by the controller. Theoretical considerations are presented and validated via EMT simulations in MATLAB/Simulink. Reliable grid operation and optimal grid support by the VSC during balanced and unbalanced grid faults can be guaranteed using the proposed algorith
Keywords: Fault ride through; grid-forming control; voltage source converter; model predictive control; current limiting